Determination of ovarian cysts in cattle with poor reproductive performance using ultrasound and plasma progesterone profile - Yimer, Nurhusien; Haron, Abd Wahid; Yusoff, Rosnina (Openventio Publishers, 2018)
Introduction: The present study investigated the occurrences of cystic ovarian diseases (COD) and abnormal ovarian cyclicity (AOC) in cows with delayed postpartum period and heifers with delayed age at first calving. Materials and Methods: A total of 102 cattle which comprised of open cows >90 days postpartum, and heifers with delayed age (>24 months) at first calving were enrolled in the study. Animals were divided into four groups according to their breeds [24 Friesian Sahiwal (FRS), 31 Bradford (BRF), 15 Brangus (BR) and 32 Kedah Kelantan (KK)]. Blood plasma samples for progesterone (P4) analysis using radioimmunoassay (RIA) were obtained twice weekly for about three months. Concurrently, the ovarian activity was also monitored for the development of dominant follicles, corpora lutea as well as any cystic ovarian condition, using a B-mode ultrasound scanner. Results: The highest incidence of AOC associated with either COD or inactive ovaries occurred in Brangus (BR; 53.3%), and the lowest incidence was observed in Kedah Kelantan (KK) cows (12.5%). The difference in AOC was significant (p<0.05) between KK and the other three breeds. In cows, the incidence of COD was highest in FRS (30%), followed by BRF (13.3%), BR (14.3%), and KK (8.7%). Overall, the incidence of COD was higher in beef heifers than in cows. Prolonged luteal phase due to luteal cysts was the predominant type of AOC in the case of FRS (66.7%) while cessation of cyclicity due to follicular cysts was the primary abnormality observed in BR (75%), and BRF (76.9%). Conclusion: This study showed that AOC and COD were the major causes of reproductive failure in both dairy and beef cattle such that the KK cows were the least affected. Moreover, differentiation among the various types of COD was possible by the combined use of P4 data and ultrasonograms.